Modulation of the capillary leakage by exogenous albumin in a rat model of endothelial glycocalyx damage - Astapenko, David; Zrzavecky, Marek; Gorskaja, Diana; Hyspler, Radomir; Ticha, Alena; Radochova, Vera; Lehmann, Christian; Malbrain, Manu L N G; Cerny, Vladimir; Hahn, Robert G (Clinical hemorheology and microcirculation, 2024)
BACKGROUND: Endothelial glycocalyx (EG) plays a crucial role in maintaining the plasma proteins within the intravascular space. OBJECTIVE: We studied whether exogenous albumin protects the EG in an experimental model of EG enzymatic damage in rats. METHODS: Rats were divided into three groups of 10 animals that received (1) Evans blue (2) Evans blue + hyaluronidase, or (3) Evans blue + hyaluronidase + 20% human albumin via the tail vein. Spectrophotometric analysis was performed 2 h later to quantify the leakage of Evans blue-labeled albumin into the heart, lungs, brain, kidneys, liver, small intestine, spleen, and skeletal muscle. RESULTS: Administration of hyaluronidase numerically increased the capillary leakage of Evans blue in all examined tissues. Co-administration of albumin decreased the leakage of albumin in all tissues except the heart. In the lungs, the ratio between the absorbance and dry organ weight decreased from 5.3 ± 2.4 to 1.7 ± 0.5 (mean ± SD) (P < 0.002), and in the liver, the absorbance decreased from 2.2 ± 0.7 to 1.5 ± 0.4 (P < 0.011). CONCLUSION: Exogenous albumin decreased the capillary leakage of albumin which was interpreted as a sign of maintained EG integrity.
Keywords: Animals; Rats, Wistar; Endothelium, Vascular; Evansova modř; Evans Blue; lidé; kapilární permeabilita; Albumins; Glycocalyx; Hyaluronoglucosaminidase; albuminy; Male; Capillary Permeability; modely nemocí na zvířatech; hyaluronoglukosaminidasa; Disease Models, Animal; krysa rodu Rattus; cévní endotel; zvířata; glykokalyx; mužské pohlaví; Rats; potkani Wistar; Humans